GROWTH PERFORMANCE OF TRANSFECTION TIGER SHRIMP BROODSTOCK Penaeus monodon IN DIFFERENT GENERATION - Hidayat Suryanto Suwoyo; . Sahabuddin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Diseases resistant genes assemblage for tiger shrimp has been initiated by The Research Institute for Coastal Aquaculture in collaboration with Bogor Agricultural Institute, through transgenesis approach under anti-virus genes transfection. The study aimed to evaluate the growth performance of broodstock candidates of tiger shrimp at different generati on (F0 and F1). This research was conducted at 2000 m2size of four ponds in Takalar Regency, South Sulawesi.. The treatment was different generations of broodstocks, which were: broodstocks originated from F0generation, (A) and F1 (B). The 22.63 to 28.57 g of broodstock candidates were stocked 0.5 ind.m-2 and then reared for 128 days. During rearing period, these shrimp were fed usingcommercial pelleted feed with content 36-38% of protein in dosage of 10-4%/ body weight. Feeding frequency was applied in the morning and in the evening. Measured variables were growth, size distribution, survival rate and water quality The results indicated that the performances of these shrimps, growth, size distributions as well as survival rates between these F0 and F1 were not significantly different (p>0.05). The growth pattern was relatively equal between treatment during rearing period. Survival rate of tiger shrimp in this study ranged from 51.7 to 73.35%. This study have implications on the provision of superior broodstock shrimp in ponds in order to support the sustainability of shrimp seed production in hatchery. Keywords: broodstock, production, transgenic, tiger shrimp